Standards of Distinctions between National and Foreign Arbitral Awards: A Discussion in The Light of Libyan Current Legislation - Omar Nayed, Murad Idris (South Asian Journal of Social Sciences and Humanities, 2023)
Arbitration is a legal process in which disputes between two or more parties are resolved by an  impartial third party, known as an arbitrator, rather than by a court of law. In the context of this  article, the legal approaches distinguishing between domestic and foreign arbitral award are  very important and they differ from one arbitration law to another. By using doctrinal legal  research methodology, this article aims to examine the legal approaches distinguishing between  domestic and foreign arbitral awards in the context of Libya. Both primary and secondary  sources are used and then analysed using critical and analytical approaches. In order to  determine the legal nature and nationality of an arbitral award, the paper has found that there  are several approaches in the study of this issue. The Libyan approach is quite outdated as it is  not in line with recent developments in the field of arbitration and international trade.  Therefore, it is recommended that Libyan lawmakers are encouraged to adopt a comprehensive  approach such as the one followed by the Model Law on International Commercial Arbitration  2006. This is vital to cope with the developments adopted by modern arbitration laws.
Keywords: Libyan Law; arbitral award; arbitration; dispute resolution